THE ANALYSIS OF CODE MIXING USED BY AGNES MO ON DEDDY CORBUZIER’S PODCAST YOUTUBE CHANNEL - Karta Atmaja (STKIP Siliwangi, 2022)
The objectives of the study are to find out the type of code mixing, the level of code mixing, and the dominant type of code mixing. This study employed content analysis which focused on the type of code mixing based on Hoffman’s theory and level of code mixing based on Suwito’s theory. The researcher found seventy-six data using inter-sentential code mixing and six data intra-lexical code mixing. The data was taken from Deddy Corbuzier’s podcast YouTube channel. The data were divided into Podcast Part I and Part II and were analyzed and documented for each Part using Hoffman’s and Suwito’s theory. The result showed that there were three forms of code mixings that found in the podcast, namely intra-sentential of code mixing, intra-lexical of code mixing and involving a change of pronunciation. In addition, it was also revealed that there are twenty-three data in word level, twenty-four data in phrase level, seven data in baster level, one data in idiom level and twenty-seven data in clause level based on Suwito’s theory. As the result, the most dominant type of code mixing is inter-sentetial code mixing type and the most dominant level of code mixing is code mixing in phrase level.